Modern Device for Amplang Maker Kalimantan Traditional Snack - Trianto, Rizki; Basuki, Puji; Purwaningrum, Shintawati Dyah; Agustin, Niyar Candra (Fakultas Teknik UM Pontianak, 2023)
Amplang is a traditional snack typical of East Kalimantan which is made from fish as the main ingredient. Innovation was carried out by adding other ingredients to obtain more attractive flavor variations and color appearances. The manual manufacturing process relies on the speed of human labor. The aim of the research was to obtain a modern amplang processing tool with a mechanical system. The machine was designed using AutoCAD, made from a 4x4 cm angle iron frame, the dough mixing chamber used a meat grinder. Initially the meat grinder was rotated by hand in this research, replaced with an electric motor, while to increase the torque, the motor speed was reduced using a reducer gear box and pulley and V belt. The results obtained in the process speed for 1 kg of dough have decreased from initially 10-15 minutes to 6-7 minutes, There was an increase of 40%. The electric motor drive source with a power of 0.5 Horse Power, while the cost of purchasing materials and tools was Rp 5,237,000 (five million two hundred thirty-seven thousand rupiah), and the working process took 112 (one hundred twelve) working hours